Prognostic Potential of the Controlling Nutritional Status (CONUT) Score in Predicting All-Cause Mortality and Major Adverse Cardiovascular Events in Patients With Coronary Artery Disease: A Meta-Analysis - Arero, Godana; Arero, Amanuel Godana; Mohammed, Shimels Hussien; Vasheghani-Farahani, Ali (Frontiers in Nutrition, 2022)
Background As defined by the Controlling Nutrition Status (CONUT) score, the prognostic significance of nutritional status has attracted attention in patients with cardiovascular disease. This meta-analysis aimed to determine the importance of CONUT score for prediction of all-cause mortality and major adverse cardiovascular events (MACE) in adult patients with coronary artery disease (CAD) Method Observational studies conducted to evaluate the association of CONUT score with adverse clinical outcomes in patients with CAD were included. We searched MEDLINE, Embase, Scopus, Cochrane library, Google scholar, medRxiv pre-print as well as Science Direct search engine for studies published from the inception of each database until March 21, 2022. Studies reporting the utility of CONUT score in the prediction of all-cause mortality and MACE among patients with CAD were eligible. The predictive potential of the CONUT score was summarized by pooling the multivariable-adjusted hazard ratio(aHR) with 95% CI for the malnourished Vs normal nutritional status or per point CONUT score increase. Result Of 2547 screened citations, nine observational studies involving 81,257 patients with CAD were analyzed. Malnutrition defined by the CONUT score was associated with significantly increased risk of all-cause mortality when compared with the normal nutritional state (aHR for mild, moderate, and severe malnutrition, respectively: (1.21 [95% CI: 1.15 to 1.27], I2=0%), (1.53 [95% CI: 1.26 to 1.84, I2=84%) and (2.24 [95% CI: 1.57 to 3.19], I2=77%). Similarly, moderate (aHR 1.71 [95% CI: 1.44 to 2.03], I2=0%) and severe (aHR 2.66 [95% CI: 1.82 to 3.89], I2=0%) malnutrition was associated with a significantly higher risk of MACE compared with the normal nutritional state. Additionally, per point increase in the CONUT score was correlated with 20 and 23% additional risk of all-cause mortality and MACE, respectively. Conclusion As defined by the CONUT score, malnutrition is an independent predictor of all-cause mortality and MACE in CAD patients. Nutritional assessment with CONUT score could allow clinicians to identify patients with CAD at high risk for adverse clinical outcomes.